KEPUASAN PASIEN TERHADAP PELAYANAN KEPERAWATAN DI RUMAH SAKIT KHUSUS DAERAH PROVINSI MALUKU - Nusawakan, Dwight; Indri Clara Lewier, Johana (Pasapua Health Journal, 2023)
Introduction: Quality service is one of the determining components of patient satisfaction at the hospital. Nurses are required to provide quality nursing services in order to increase patient satisfaction. Nursing services are professional services provided by nurses in accordance with service standards where the services received exceed patient expectations. Thus nurses must be able to provide the best nursing services to patients. Method: The type of research conducted in this study is qualitative research that uses a phenomenological approach. Data collection from this study was obtained by Observation, Interview and Documentation techniques. The number of informants in this study was 10 people using the Convenience Sampling Technique chosen according to the purpose of the study, who are patients who are currently being treated at the RSKD Provinsi Maluku, then given 31 substance questions from 4 variables related to patient satisfaction with nursing services in the RSKD Provinsi Maluku. This research was conducted on 19 September – 11 October 2022. Results: The results of this study indicate that there are 4 factors that determine patient satisfaction with nursing services at the RSKD Provinsi Maluku, namely health facilities, service quality, communication and availability of nursing staff. Conclusion: of the four factors that have been explained based on the results of the research conducted, it was found that the patients were satisfied with the nursing services provided at the RSKD Provinsi Maluku, but there were several things that needed to be considered in carrying out nursing services, namely the availability of drugs that were not sufficient for patients at home pharmacies sick and the drug collection service at the pharmacy is rather long.